Biosynthesis of the psychotropic plant diterpene salvinorin A: Discovery and characterization of the Salvia divinorum clerodienyl diphosphate synthase. (6th February 2017) - Pelot, Kyle A.; Mitchell, Rod; Kwon, Moonhyuk; Hagelthorn, Lynne M.; Wardman, Jacob F.; Chiang, Angela; Bohlmann, Jörg; Ro, Dae‐Kyun; Zerbe, Philipp
Summary: Salvia divinorum commonly known as diviner's sage, is an ethnomedicinal plant of the mint family (Lamiaceae). Salvia divinorum is rich in clerodane‐type diterpenoids, which accumulate predominantly in leaf glandular trichomes. The main bioactive metabolite, salvinorin A, is the first non‐nitrogenous natural compound known to function as an opioid‐receptor agonist, and is undergoing clinical trials for potential use in treating neuropsychiatric diseases and drug addictions. We report here the discovery and functional characterization of two S. divinorum diterpene synthases (diTPSs), the ent ‐copalyl diphosphate ( ent ‐CPP) synthase SdCPS1, and the clerodienyl diphosphate (CLPP) synthase SdCPS2. Mining of leaf‐ and trichome‐specific transcriptomes revealed five diTPSs, two of which are class II diTPSs (SdCPS1‐2) and three are class I enzymes (SdKSL1‐3). Of the class II diTPSs, transient expression in Nicotiana benthamiana identified SdCPS1 as an ent ‐CPP synthase, which is prevalent in roots and, together with SdKSL1, exhibits a possible dual role in general and specialized metabolism. In vivo co‐expression and in vitro assays combined with nuclear magnetic resonance (NMR) analysis identified SdCPS2 as a CLPP synthase. A role of SdCPS2 in catalyzing the committed step in salvinorin A biosynthesis is supported by its biochemical function, trichome‐specific expression and absence of additional class II diTPSs in S. divinorum . Structure‐guided mutagenesis revealed four catalytic residues that enabled the re‐programming of SdCPS2 activity to afford four distinct products, thus advancing our understanding of how neo‐functionalization events have shaped the array of different class II diTPS functions in plants, and may promote synthetic biology platforms for a broader spectrum of diterpenoid bioproducts. Significance statement: The diterpene Salvinorin A is an opioid‐receptor agonist with potential applications for treatment of neuropsychiatric diseases and drug addictions. The discovery of genes and enzymes of Salvinorin A biosynthesis will enable synthetic biology approaches for its production in metabolically engineered heterologous hosts or for improved production in S. divinorum .